ANALISIS KEABSAHAN DAN KEPASTIAN HUKUM PERJANJIAN KERJA PEKERJA MIGRAN INDONESIA DENGAN PERUSAHAAN PENEMPATAN SEBELUM BEKERJA DI LUAR NEGERI (Studi pada LPK Progres Inti Solusi) - Ajat Sudrajat; Desi Syamsiah; Fatma Ayu Jati Putri (Journal of Innovation Research and Knowledge, 2026)
This study aims to identify and analyze the legal validity requirements of employment agreements between prospective Indonesian Migrant Workers and LPK Progres Inti Solusi prior to overseas employment based on Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and its implementing regulations. Furthermore, this study analyzes legal certainty within employment agreements concerning the rights and obligations of both parties. This research uses a normative legal research method with statutory and conceptual approaches. The data used are secondary data obtained from primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques were conducted through literature studies and analyzed qualitatively. The results show that the validity of employment agreements between prospective Indonesian Migrant Workers and LPK Progres Inti Solusi is determined by the fulfillment of the legal requirements of agreements as stipulated in Article 1320 of the Indonesian Civil Code and Article 14 of Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. The clarity of work elements, wages, and instructions in employment contracts constitutes the primary basis for legal protection. Violations regarding working hours, illegal deductions, or misleading job descriptions may render the agreement null and void. In addition, the employment agreements studied have fulfilled the principle of legal certainty through synchronization between Indonesian national law and the laws of the destination country, namely Japan. The use of bilingual contract formats and Japanese industrial standards minimizes ambiguity and strengthens legal protection for Indonesian migrant workers.